Pengaruh Budaya Kaizen Dan Motivasi Terhadap Kinerja Karyawan Pada PT Buma Cima Nusantara Lampung Utara - Yateno; Suwarto; Lexsi Susandi (Jurnal Manajemen DIVERSIFIKASI, 2024)
Employee performance is high, and this is where Kaizen work culture and work motivation play an important role in influencing employee performance. So much needed research on Kaizen culture and motivation on employee performance. Work culture motivates employees to bring out the best in what the organization gives them to improve their performance and provide the best results for the company/organization. The purpose of this study was to determine the joint influence of Kaizen culture and work motivation on the performance of PT. Buma Cima Nusantara. In this study using primary data and secondary data, the research method used is the technique used in Probability Sampling is Sampling Random Sampling, namely taking sample members from the population at random without regard to the existing strata in the population, with a total sample of 108 people. . The data analysis technique used is validity test, reliability test, normality test, linearity test and homogeneity test. Testing the analytical model in this study using multiple linear regression analysis, T test, F test and R determination. Based on the results of the study using the T test, it was found that the kaizen culture had no and insignificant effect on employee performance at PT Buma Cima Nusantara Bunga Mayang North Lampung, motivation had a significant effect on employee performance at PT Buma Cima Nusantara Bunga Mayang North Lampung. From the F test, it is found that the kaizen culture and motivation together have a significant and significant effect on the performance of employees at PT Buma Cima Nusantara Bunga Mayang, North Lampung.